The effect of strong carbide-forming elements such as Mo, Ti, V and Nb on the microstructure of ferritic stainless steel - Kuzucu, V; Aksoy, M; Korkut, MH (Elsevier Science Sa, 1998)
The effects of both stabilizing elements such as Mo, Ti, V and Nb and of homogenization on microstructure, thermal properties, and some mechanical properties of ferritic stainless steels containing 18 wt.% Cr were investigated using scanning electron microscopy, energy-dispersive spectrometry, X-ray diffraction, differential thermal analysis, microhardness measurements and Charpy V notch impact tests. These stabilizing elements formed hard MC carbides, but decreased the amount of M23C6 carbides that were forming to too great a degree in the ferritic stainless steel considered. In addition, they also reduced the dissolving temperature of the M23C6 carbides, the grain coarsening temperature of the ferrite phase (except for V), and the toughness of the samples, but increased the microhardness. Homogenization increased the microhardness, but it did not affect the toughness considerably. (C) 1998 Elsevier Science S.A. All rights reserved.
Keywords: microstructure; stabilizing elements; stainless steel